2011
DOI: 10.1007/s00401-011-0801-7
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular drainage of solutes is impaired in the ageing mouse brain and in the presence of cerebral amyloid angiopathy

Abstract: The deposition of amyloid-β (Aβ) peptides in the walls of leptomeningeal and cortical blood vessels as cerebral amyloid angiopathy (CAA) is present in normal ageing and the majority of Alzheimer's disease (AD) brains. The failure of clearance mechanisms to eliminate Aβ from the brain contributes to the development of sporadic CAA and AD. Here, we investigated the effects of CAA and ageing on the pattern of perivascular drainage of solutes in the brains of naïve mice and in the Tg2576 mouse model of AD. We repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
321
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 300 publications
(340 citation statements)
references
References 67 publications
15
321
1
3
Order By: Relevance
“…17,18 More recent models have suggested that A in CAA is predominantly generated by neurons [19][20][21] and subsequently deposited in the vessel wall because of impairment in A clearance. Impaired A clearance may be caused by alterations in perivascular drainage pathways [22][23][24] and deficits in endothelial-mediated active transport of A into the blood. 25 Factors such as age-related arterial stiffening may contribute to the failure of perivascular drainage of A .…”
Section: Pathologic Manifestation Of Cerebral Amyloid Angiopathymentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 More recent models have suggested that A in CAA is predominantly generated by neurons [19][20][21] and subsequently deposited in the vessel wall because of impairment in A clearance. Impaired A clearance may be caused by alterations in perivascular drainage pathways [22][23][24] and deficits in endothelial-mediated active transport of A into the blood. 25 Factors such as age-related arterial stiffening may contribute to the failure of perivascular drainage of A .…”
Section: Pathologic Manifestation Of Cerebral Amyloid Angiopathymentioning
confidence: 99%
“…Thromboses, atherosclerosis, or arterial stiffening may abolish the motive force necessary for drainage of A through interstitial fluid pathways, which in turn enhances the accumulation of amyloid in the vessel wall. 23,24,57,91 The hypothesis that common age-related vascular diseases, such as atherosclerosis and arterial stiffening, trigger vascular amyloid deposition could also explain the rapid increase in the prevalence of CAA with aging. 3 An imaging marker of impaired clearance of interstitial fluid is dilated perivascular spaces.…”
Section: Pathophysiologic Mechanisms Of Ischemia In Cerebral Amyloid mentioning
confidence: 99%
“…Extracellular matrix (ECM) properties in the vessel wall are important for this perivascular filter by forming and maintaining basement membranes. The basement membranes are important for regulating cell growth, differentiation, and migration and consist of laminins, nidogens, collagen, and heparan sulfate proteoglycans (HSPGs) (Hawkes et al, 2011). HSPGs co-localize with the vascular deposits in AD and HCHWA-D (Van Horssen et al, 2001).…”
Section: The Role Of Extracellular Matrix Components In Cerebral Amylmentioning
confidence: 99%
“…Age-related changes in levels of laminin, fibronectin, and perlecan have been reported in mouse brain capillaries (Hawkes et al, 2011). Vacuolization, reduplication, and thickening of capillary basement membranes have also been shown to occur in the human aged and AD brain (Perlmutter, 1994;Shimizu et al, 2009).…”
Section: Introductionmentioning
confidence: 98%